Phytochemical components and antibacterial activity of two populations of Senecio vulgaris L. essential oils as traditional medicine plant - Fatemeh Hajmoradi; Hamed Fathi; Foozieh Moghadami (Iranian Journal of Microbiology)
Background and Objectives: Senecio vulgaris L., a member of the Asteraceae family, has been widely employed in traditional Iranian herbal practices for centuries. This research seeks to analyze and compare the essential oil compositions and antibacterial characteristics of two distinct populations of S. vulgaris. Materials and Methods: Essential oils were obtained from the above-ground parts of these populations through hydrodistillation, and their chemical constituents were examined using gas chromatography-mass spectrometry. The antibacterial effectiveness of the essential oils against both Gram-positive and Gram-negative bacteria was evaluated employing the agar well diffusion technique. Results: Monoterpene hydrocarbons were found to be dominated in both populations, with Humulene epoxide II being the primary constituent, constituting 17.87% in the first population and 21.55% in the second one. The agar-well diffusion method revealed significant antibacterial effects of the S. vulgaris essential oils. The findings indicated that the essential oil displayed heightened activity against Escherichia coli in both populations. Furthermore, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) tests indicated that Pseudomonas aeruginosa with concentrations of 400 µg/mL for both tests, was the most susceptible bacteria, while Streptococcus pyogenes with MIC = 800 and MBC>800 µg/mL was the most resistant in both populations of S. vulgaris. Conclusion: This research highlights the significance of S. vulgaris as a valuable reservoir of monoterpene-rich oil exhibiting robust antibacterial characteristics, suggesting its potential use in the development of novel and naturally derived therapeutics for bacterial diseases.